Analisis Kemampuan Pemecahan Masalah Ditinjau dari Self-Efficacy Matematis: Studi pada Siswa Kelas VIII SMP SMP Negeri 16 Sungai Raya - Wahyu Anggraini; Ahmad Yani T; Nurfadilah Siregar; Nadya Febriani Meldi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Problem solving skill is an essential component of mathematics learning. However, in reality, students's problem-solving skills are still low. Internal factors are among the causes that affect students in learning mathematics. One of these internal factors is mathematical self-efficacy. This study aims to examine mathematical problem solving skill in relation to the mathematical self-efficacy of eight-grade students at SMP Negeri 16 Sungai Raya on the topic of linear equations in two-variable. The method used in this research is qualitative descriptive, with data collection techniques including questionnaires, written tests, and interviews. The subjects of study consisted of 6 students representing each category of mathematical self-efficacy. The results indicate that students with high mathematical self-efficacy have very good problem-solving skills. Students with moderate mathematical self-efficacy demonstrate good problem-solving skills, although they have not maximally met all problem-solving indicators. Meanwhile, students with low mathematical self-efficacy exhibit less satisfactory problem-solving skills.